The Influences of “Public Speaking-Attractive Training” to the Public Speaking Anxiety (PSA) - Wati, Nenden Lesmana; Yosep, Iyus; Dharmansyah, Dhika; Ibrahim, Masdum (KnE Life Sciences, 2021)
Public speaking is very important for nursing students because they are expected to become good health promotors in the future, such skills are therefore extremely helpful for career development prospects, though the act of public speaking can be daunting. The purpose of this study is to determine the effect of public speaking attractive training on Public Speaking Anxiety (PSA). The design of this research is pre-experimental, with one group pre- and post-test. The population of this study is comprised of 20 nursing students who were members of the College Collaboration Organization. The total sampling technique was used. Training focused on personal strength and public delivery. Pre- and post-training were measured using the Personal Report of Public Speaking Anxiety (PRPSA), instrument modified from McCroskey, J. C. (2013). Generally, there was a marked a decrease in the level anxiety displayed by participants. This study showed that public speaking training had a positive impact on reducing PSA. Keywords: Public Speaking, Attractive training, Anxiety, Nursing Students.